The power of the mine : a transformative opportunity for Sub-Saharan Africa - Banerjee, Sudeshna Ghosh, 1973- (Directions in development (Washington, D.C.), 2015)
Africa needs power - to grow its economies and enhance the welfare of its people. Power for all is still a long distance away - two thirds of the population remains without electricity and enterprises rank electricity as a top constraint to doing business. This sub-optimal situation coexists while vast energy resources remain untapped. One solution to harness these resources could be to tap into the concept of anchor load. Mining industry lends itself to the concept of anchor load as it needs power in large quantity and reliable quality to run its processes. Underpinned by a comprehensive data.